Marketing Innovations in Enhancing the Sustainability of the Creative Market in Metro City - Aziz Hanif Mahfud; Madnasir; Erike Anggraeni (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research examines the role of marketing innovation in enhancing the sustainability of the creative market in the digital era. Through a systematic literature review, this study aims to identify current trends, best practices, and challenges in implementing innovative marketing strategies in the creative industry. The analysis covers various aspects of marketing innovation, including digital technology adoption, value-based strategies, consumer collaboration, and integration of online-offline experiences. Research findings indicate that digital transformation has become a primary driver of marketing innovation, with the utilization of artificial intelligence, virtual reality, and blockchain opening new opportunities for personalization and creativity in marketing. A significant shift towards value-based and sustainable marketing strategies is identified as a response to consumer demands for ethical and sustainable products and services. Collaboration and co-creation with consumers emerge as effective approaches to enhance product relevance and build customer loyalty. Adaptability and flexibility of marketing strategies prove crucial in facing rapidly changing market dynamics. Seamless integration between online and offline marketing is found to be key in creating holistic customer experiences. This study concludes that marketing innovation plays a vital role in enhancing the competitiveness and sustainability of the creative industry. Recommendations include investing in digital capabilities, developing value-based strategies, strengthening consumer collaboration, increasing organizational flexibility, and optimizing the integration of online-offline strategies. The implications of this research are relevant for creative industry practitioners, policymakers, and researchers in the fields of marketing and creative industries.